1994
DOI: 10.1524/ract.1994.6667.special-issue.29
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison Between Unirradiated UO2(s) and Schoepite Solubilities in 1 Μ NaCl Medium

Abstract: In this study, the dissolution of unirradiated U0 2 (s) under oxidizing conditions (5% 0 2 /N 2 ) in 1 Μ NaCl was investigated at neutral pH. A decrease in pH and subsequent return to neutrality led to the formation of a yellow solid phase precipitated on the U0 2 (s) surface, closely resembling schoepite, U0 2 (0H) 2 • H 2 0(S), (chemically equivalent to U0 3 · 2H 2 0(s)). The uranium concentrations measured in solutions matched schoepite solubility. These solubility data have been compared with the values ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 15 publications
(22 reference statements)
2
16
0
Order By: Relevance
“…This agrees with studies showing the formation of U colloids in solutions where polynuclear aqueous U(VI) species pre-exist ( Fig. 2) and of meta-stable uranyl oxide hydrates in super-saturated solutions (Dent et al, 1992;Torrero et al, 1994;DiazArocas and Grambow, 1998). The major assessment of our experimental work is that sorption onto large surface areas of Al-hydroxide controls the removal of U from aqueous phase for such unstable solutions at ½U I AQ P 10 lM, as well as for the stable uranyl solutions.…”
Section: Macroscopic Uranyl Uptakesupporting
confidence: 91%
See 1 more Smart Citation
“…This agrees with studies showing the formation of U colloids in solutions where polynuclear aqueous U(VI) species pre-exist ( Fig. 2) and of meta-stable uranyl oxide hydrates in super-saturated solutions (Dent et al, 1992;Torrero et al, 1994;DiazArocas and Grambow, 1998). The major assessment of our experimental work is that sorption onto large surface areas of Al-hydroxide controls the removal of U from aqueous phase for such unstable solutions at ½U I AQ P 10 lM, as well as for the stable uranyl solutions.…”
Section: Macroscopic Uranyl Uptakesupporting
confidence: 91%
“…Note that low U coverage samples were obtained over ranges of ½U I AQ values (1-100 lM). Torrero et al (1994) Values are at 298 K and at infinite dilution standard state. a Value selected in the thermodynamic data compilation of Grenthe et al (1992) and confirmed in the revised selection of Guillaumont et al (2003).…”
Section: Presentation Of the Spectroscopic Samplesmentioning
confidence: 99%
“…The value of the solubility product of schoepite at 25°C was experimentally determined by Torrero et al (1994): K schoepite = 10 5.38 . In order to calculate saturation indices with respect to schoepite using equation (2), it is necessary to know the activity of the uranyl cation, a(UO 2+ 2 ), and the pH of the solutions.…”
Section: Identification Of Minerals On the Surface Of Calcitementioning
confidence: 99%
“…Thermodynamic data for aqueous uranyl species and solubility constants of U-bearing solid phases were adjusted to be consistent with the NEA database [27]. The formation constant of UO 2 (OH) 2 [28] and solubility constant of "amorphous" schoepite from Torrero et al [29] were also added to the database. Calculation of U speciation shows that more than 96% of the U VI occur as uranyl ions (UO 2+ 2 ) in the experimental suspensions over the entire range of U concentration.…”
Section: The Removed Quantity Of Uranyl Ion (Uo 2+mentioning
confidence: 99%